Pengaruh Audit Fee, Ukuran Kantor Akuntan Publik, Audit Tenure, Dan Independensi Auditor Terhadap Kualitas Audit - Karina Amalia; Khuzaeni Khuzaeni (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of audit fee, Public Accounting Firm size, audit tenure, and auditor independence on audit quality. This research employed a quantitative approach using secondary data in the form of annual financial statements of food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2025 period. The population consisted of 98 companies. The samples were selected using the purposive sampling method, resulting in 19 sample companies observed over a six-year period, with a total of 114 observations. The data were analyzed using logistic regression with the assistance of EViews 13 software. The results indicate that audit fee, Public Accounting Firm (KAP) size, and auditor independence have a significant effect on audit quality, while audit tenure has no significant effect on audit quality. Furthermore, audit fee, Public Accounting Firm (KAP) size, audit tenure, and auditor independence simultaneously have a significant effect on audit quality.